2007
DOI: 10.1152/ajpregu.00734.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CCK-1 receptor blockade on ghrelin and PYY secretion in men

Abstract: . Effect of CCK-1 receptor blockade on ghrelin and PYY secretion in men. Am J Physiol Regul Integr Comp Physiol 292: R1391-R1399, 2007. First published November 30, 2006; doi:10.1152/ajpregu.00734.2006, peptide YY (PYY), and ghrelin have been proposed to act as satiety hormones. CCK and PYY are stimulated during meal intake by the presence of nutrients in the small intestine, especially fat, whereas ghrelin is inhibited by eating. The sequence of events (fat intake followed by fat hydrolysis and CCK release)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 38 publications
3
82
0
1
Order By: Relevance
“…Ghrelin secretion is also inhibited by somatostatin, potentially involving SSTR1, -2, and -3 (48). The effects of other gut hormones on ghrelin release are varied (95)(96)(97). GIP, for example, has been reported as both an inhibitor and stimulator of ghrelin secretion.…”
Section: Sensing Of Non-nutrient Stimulimentioning
confidence: 99%
“…Ghrelin secretion is also inhibited by somatostatin, potentially involving SSTR1, -2, and -3 (48). The effects of other gut hormones on ghrelin release are varied (95)(96)(97). GIP, for example, has been reported as both an inhibitor and stimulator of ghrelin secretion.…”
Section: Sensing Of Non-nutrient Stimulimentioning
confidence: 99%
“…Appetite-suppressant effects of duodenal lipids are dependent on fat digestion, so fat digestion may also be a prerequisite for fat-induced stimulation of PYY (34) . Indeed, blocking the hydrolysis of long-chain fatty acids abolishes the typical PYY postprandial response, probably due to a lack of CCK release (29) . Other foods or substances have also been tested for potential PYY responses.…”
Section: Functions Of Peptide Yymentioning
confidence: 99%
“…Because PYY release is affected by CCK levels (29) , it is possible that the effect of fatty acid composition on PYY is an indirect one through CCK. In the study mentioned above by Robertson et al (122) it was shown that peak CCK release after a high-fat meal challenge was greatest with a meal rich in SFA compared with either MUFA or PUFA.…”
Section: Dietary Fatty Acids and Peptide Yymentioning
confidence: 99%
“…It stimulates gallbladder contraction and pancreatic enzyme secretion, and retards gastric emptying [82,83]. Furthermore, the release of PYY and GLP-1, after lipid ingestion, is dependent on signaling through the CCK receptor [84,85]. In the CNS, the gastrin receptor seems to be the main receptor; and the effects of CCK-8 and CCK-5 are probably mediated through this receptor as only trace amounts of gastrin are found in the CNS [80,86].…”
Section: Cholecystokininmentioning
confidence: 99%